2021
DOI: 10.1021/acs.jpca.1c05846
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Spectroscopy of Size-Selected Bismuth–Boron Clusters: BiBn (n = 6–8)

Abstract: Because of its low toxicity, bismuth is considered to be a "green metal" and has received increasing attention in chemistry and materials science. To understand the chemical bonding of bismuth, here we report a joint experimental and theoretical study on a series of bismuth-doped boron clusters, BiB n − (n = 6−8). Well-resolved photoelectron spectra are obtained and are used to understand the structures and bonding of BiB n − in conjunction with theoretical calculations. Global minimum searches find that all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 69 publications
4
26
0
Order By: Relevance
“…E-mail: leesxoptics@163.com b College of Physics, Guizhou University, Guiyang 550025, Guizhou, People's Republic of China structures, but had been unable to experimentally determine the existence of caged boron clusters. In 2014, the cage-type allboron cluster borospherene B 40 À was experimentally found. 15 Borospherene B 40 À exhibits a hollow cage-like structure, but has different electronic structures and properties from C fullerenes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…E-mail: leesxoptics@163.com b College of Physics, Guizhou University, Guiyang 550025, Guizhou, People's Republic of China structures, but had been unable to experimentally determine the existence of caged boron clusters. In 2014, the cage-type allboron cluster borospherene B 40 À was experimentally found. 15 Borospherene B 40 À exhibits a hollow cage-like structure, but has different electronic structures and properties from C fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to fullerenes, doped (especially for mono-atom) boron clusters can produce new structures or properties. 18,[20][21][22][28][29][30][31][32][33][34][35][36][37][38][39][40][41] For example, B 20 À , B 22 À , and B 24 have a quasiplanar, quasi-planar, and double-ring tubular structure, 10,42 respectively. However, aer adding alkali metal atoms, both LiB 20 À and MB 22 À (M ¼ Na, K) possess a double-ring tubular structure and Li 2 B 24 possesses a three-ring tubular structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 A similar structure was experimentally confirmed for B 6 Bi − , whose double antiaromaticity favors the planar elongated chain. 85 With Zr, the hexagonal B framework bends in a boat-like conformation engulfing the TM. 66…”
Section: Introductionmentioning
confidence: 99%
“…Similar to fullerenes, doping of metal atoms into boron clusters can produce new structures or properties. , , For example, in the case of an alkali metal, experimental research combined with theoretical calculation revealed that B 20 – , B 22 – , and B 24 have a quasi-planar structure, quasi-planar structure, and double-ring tubular structure, , respectively. However, both LiB 20 – and MB 22 – (M = Na and K) possess a double-ring tubular structure and Li 2 B 24 possesses a three-ring tubular structure. ,, In addition, Li-, Na-, or K-doped borospherene B 40 is expected to become a nonlinear optical (NLO) nanomaterial .…”
Section: Introductionmentioning
confidence: 99%